Makassarese and English Affirmative Sentences Pattern : A Linguistic Contrastive Study - A. Ardiansyah; Sudirman Maca; Syahriah Madjid (Humaniora: Journal of Linguistics, Literature, and Education, 2021)
This research aims to determine the differences between Makassarese and English structure. This research is a descriptive qualitative research with ten samples of native speakers of Makassarese in urban village of PAI, Biringkanaya Makassar. The method used is contrastive method and using sentence function theory from Verhaar and the theory of tree diagram from Bornstain. The results of this research indicate the existence of different Makassarese and English structurally in terms of sentence function. The affirmative sentences in Makassarese generally begins with the predicate (P) then followed by subject (S) whils English sentences begins with subject (S) then followed by predicate (P). Verb in Makassarese also cannot change or get modification because it is not affected by an adverb and context of the sentence. While the verb in English can change depending on an adverb and context of the sentence.